PENERAPAN HUKUM PADA MANAJEMEN PEMBIAYAAN PENDIDIKAN DASAR DI INDONESIA - Budaya, Budi (FKIP Universitas Wisnuwardhana, 2018)
For Indonesia, guarantee of access to education has actually become a commitment between the government and the community that is in line with the state's goal of educating the life of the nation. To achieve these objectives the implementation of education requires a clear legal basis, especially related to the management of finance. This research was conducted in a cross-case approach to how to integrate and compare findings from research cases. This procedure refers to a constant comparative method by combining between cases, that cross-case analysis is done by comparing with cases I, II and III. By using this method, the research findings in the first case are formulated into propositions. The findings of this study indicate that school management uses a participatory leadership model. Participatory leadership is done in a persuasive way, creating harmonious cooperation, fostering loyalty, and participation of subordinates. In addition to participatory leadership, school management is trying to refer to the concept of School Based Management (SBM) in managing schools. SBM is defined as a form of education management autonomy in the education unit in this case the principal or madrasah and the teacher is assisted by a school or madrasah committee in managing educational activities. Management of education units at the level of primary and secondary education implements school-based management as indicated by independence, partnership, participation, openness, and accountability.Keywords: application of the law, financing management, basic education